Month – to – Month Until N Years Prediction for Planning a Productive Firm - Fahad, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper offers a monthly prediction method for planning production, inventory, workforce, sales and prices until N years. Each monthly decision will depend on last month, decisions and take in consideration the future forecasted demand. The manager can run the program in any month within a year. This method is executed by computer programming technique to maximize profits.